Vocabulary learning strategies, vocabulary skills, and integrative motivation levels among university students in Batam - Susanto, Alpino (2018)
The Basic elements that contribute to the English proficiency are motivation and vocabulary learning strategies. Yet these two elements are generally acknowledged among language teachers and learners as an essential factor in language competence, but paid less attention in the learning process practicality. This research aimed to examine vocabulary learning strategies, integrative motivation, and vocabulary skills among university students in Batam, Indonesia. Vocabulary learning strategies and integrative motivation were independent variables, while vocabulary skills were the dependent variable. This research used quantitative approach. Two questionnaires were used to measure vocabulary learning strategies and integrative motivation, while a test was conducted to measure the level of vocabulary skills. The questionnaire and test were adapted and modified from previous studies. The validity of the data in this research has been verified by language experts and the reliability by pilot test. There were 314 samples. The research revealed the finding on the vocabulary learning strategies through integrativeness and attitudes toward learning situation toward vocabulary skills. The research proposes a new model of vocabulary learning strategies through integrativeness and attitudes toward learning situation toward vocabulary skills. The students with the higher strategies to expand the knowledge of new vocabulary items can ideally have higher level of integrativeness and attitudes to learning situation to achieve higher vocabulary skills. Overall as a conclution, to master the vocabulary, leaners should focus on vocabulary learning strategies as well as integrative motivation.